Efficacy and safety of bromfenac 0.09% and sodium hyaluronate 0.4% combination therapy, versus placebo in patients with pterygium I–III for clinical signs on ocular inflammation - Chávez-Mondragón E (Dove Medical Press, 2019)
Eduardo Chávez-Mondragón,1 Claudia Palacio,2 Abraham Soto-Gómez,3 Miguel Villanueva-Nájera,4 Guillermo De Wit-Carter,5 Ruben Suárez-Velasco,6 Leopoldo Baiza-Duran,7 Oscar Olvera-Montaño,7 Patricia Muñoz-Villegas71Fundación de Asistencia Privada Conde de Valenciana, IAP, CDMX, Mexico; 2Fundación Hospital Nuestra Señora de la Luz, IAP, CDMX, Mexico; 3Catarata y Glaucoma de Occidente, SA de CV, Guadalajara, Jalisco, Mexico; 4Private Office, CDMX, Mexico; 5Asociación para Evitar la Ceguera en Mexico IAP, CDMX, Mexico; 6Novam y Vita, Guadalajara, Jalisco, Mexico; 7Clinical Research Department, Laboratorios Sophia, SA de CV, Zapopan, Jalisco, MexicoPurpose: This study evaluated the clinical efficacy and safety of bromfenac 0.09%, sodium hyaluronate 0.4% (SH) combination therapy, versus placebo and SH in a clinical model of pterygium I–III.Methods: A total of 166 eyes (99 patients) with pterygium grade I–III were randomized to bromfenac 0.09% ophthalmic solution+SH 0.4% or placebo+SH 0.4%. This was a Phase IV, prospective, parallel, double-masked, multicenter clinical trial. One drop of bromfenac or placebo was instilled two times a day (BID) for 20 days, both groups accompanied treatments with one drop of SH three times a day (TID). The primary efficacy endpoints were the conjunctival hyperemia and the Ocular Surface Disease Index (OSDI) score. Other results measured included burning, foreign body sensation, and photophobia. The safety was assessed by the tear break-up time (TBUT), visual acuity (VA), IOP, lissamine green, fluorescein stains, and the incidence of adverse events (AEs).Results: Compared with baseline, there was a significant reduction in the conjunctival hyperemia (p=0.0001) and OSDI score in both groups (p=0.0001). There was a significant improvement in ocular symptomatology for both, placebo/SH and bromfenac/SH groups (p=0.0001), the decrement in the ocular burning was 41.1% vs 24.6%, the foreign body sensation was 31.5% vs 36.2% and, for photophobia was 23.3% vs 30.5%, respectively. A statistically significant difference was observed in TBUT for bromfenac/SH (p=0.045), at day 20. There were no significant alterations in IOP (p=0.068) or VA (p=0.632). Similar improvements were observed in the fluorescein and green lissamine staining. Finally, the incidence of AE was similar between groups.Conclusion: The treatment with bromfenac 0.09% ophthalmic solution and SH 0.4% combination therapy for 3 weeks reduced clinical signs, in patients with pterygium I–III. The results suggest that bromfenac 0.09% can improve the symptomatology, reduce the presentation of clinical signs associated with superficial ocular inflammation.Keywords: nonsteroidal anti-inflammatory drug, Ocular Surface Disease Index, conjunctival hyperemia, ocular lubricant